Westonci.ca is your trusted source for accurate answers to all your questions. Join our community and start learning today! Discover in-depth answers to your questions from a wide network of experts on our user-friendly Q&A platform. Discover detailed answers to your questions from a wide network of experts on our comprehensive Q&A platform.
Sagot :
To determine the values of the function [tex]\( h(x) \)[/tex] at [tex]\( x = 0 \)[/tex] and [tex]\( x = 4 \)[/tex], we need to refer to the piecewise definition of the function [tex]\( h \)[/tex].
1. For [tex]\( x = 0 \)[/tex]:
- Based on the definition, when [tex]\( 0 \leq x < 4 \)[/tex], the function [tex]\( h(x) = 2x^2 - 3x + 10 \)[/tex].
- Plug in [tex]\( x = 0 \)[/tex] into this part of the function:
[tex]\[ h(0) = 2(0)^2 - 3(0) + 10 \][/tex]
- Simplifying,
[tex]\[ h(0) = 0 - 0 + 10 = 10 \][/tex]
2. For [tex]\( x = 4 \)[/tex]:
- Based on the definition, when [tex]\( x \geq 4 \)[/tex], the function [tex]\( h(x) = 2^x \)[/tex].
- Plug in [tex]\( x = 4 \)[/tex] into this part of the function:
[tex]\[ h(4) = 2^4 \][/tex]
- Simplifying,
[tex]\[ h(4) = 16 \][/tex]
Thus, the values of the function are:
[tex]\[ \begin{array}{l} h(0) = 10 \\ h(4) = 16 \end{array} \][/tex]
1. For [tex]\( x = 0 \)[/tex]:
- Based on the definition, when [tex]\( 0 \leq x < 4 \)[/tex], the function [tex]\( h(x) = 2x^2 - 3x + 10 \)[/tex].
- Plug in [tex]\( x = 0 \)[/tex] into this part of the function:
[tex]\[ h(0) = 2(0)^2 - 3(0) + 10 \][/tex]
- Simplifying,
[tex]\[ h(0) = 0 - 0 + 10 = 10 \][/tex]
2. For [tex]\( x = 4 \)[/tex]:
- Based on the definition, when [tex]\( x \geq 4 \)[/tex], the function [tex]\( h(x) = 2^x \)[/tex].
- Plug in [tex]\( x = 4 \)[/tex] into this part of the function:
[tex]\[ h(4) = 2^4 \][/tex]
- Simplifying,
[tex]\[ h(4) = 16 \][/tex]
Thus, the values of the function are:
[tex]\[ \begin{array}{l} h(0) = 10 \\ h(4) = 16 \end{array} \][/tex]
Answer:
To determine the values of the function \( h(x) \) at \( x = 0 \) and \( x = 4 \), we need to refer to the piecewise definition of the function \( h \).
1. For \( x = 0 \):
- Based on the definition, when \( 0 \leq x < 4 \), the function \( h(x) = 2x^2 - 3x + 10 \).
- Plug in \( x = 0 \) into this part of the function:
\[
h(0) = 2(0)^2 - 3(0) + 10
\]
- Simplifying,
\[
h(0) = 0 - 0 + 10 = 10
\]
2. For \( x = 4 \):
- Based on the definition, when \( x \geq 4 \), the function \( h(x) = 2^x \).
- Plug in \( x = 4 \) into this part of the function:
\[
h(4) = 2^4
\]
- Simplifying,
\[
h(4) = 16
\]
Thus, the values of the function are:
\[
\begin{array}{l}
h(0) = 10 \n
h(4) = 16
\end{array}
\]
Step-by-step explanation:
We appreciate your time. Please come back anytime for the latest information and answers to your questions. Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. We're dedicated to helping you find the answers you need at Westonci.ca. Don't hesitate to return for more.